Retrospective study of inguinal hernia repair without drainage - Jadav, Jayeshkumar S.; Kotwal, Shubham R. (International Surgery Journal, 2018)
Background: A common method for treatment of inguinal hernia is surgical repair using prosthesis. Aim of this study is to evaluate that whether there is need for post-operative drainage of hernia wound or not and various complications of putting drain into hernia wound. Methods: A case study of 50 patients with predominant complain of inguinal swelling fulfilling the required selection criteria which were admitted in Guru Govind Singh Hospital, M P Shah Medical College, Jamnagar, during period of 2014 to 2016 are studied retrospectively. Drain were not put in any of the patient and findings were recorded. Results: It is found that most of patient recover well, only 8%of patients had wound infection and 2 patients having seroma. Conclusions: It reflects that there is no need to put drain routinely in inguinal hernia surgery.